2015
DOI: 10.1016/j.eneco.2015.03.024
|View full text |Cite
|
Sign up to set email alerts
|

The impact of advanced biofuels on aviation emissions and operations in the U.S.

Abstract: The MIT Joint Program on the Science and Policy of Global Change combines cutting-edge scientific research with independent policy analysis to provide a solid foundation for the public and private decisions needed to mitigate and adapt to unavoidable global environmental changes. Being data-driven, the Program uses extensive Earth system and economic data and models to produce quantitative analysis and predictions of the risks of climate change and the challenges of limiting human influence on the environment-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Xiao et al (2013) showed that the direct impact of local government spending on CO 2 emissions was significantly negative in China [31]. Fritzsche and Jeff (2013) described a revision of the 2002 greenhouse gas emission reduction expenditure estimates made by Canadian businesses [32] , and Galinato and Galinato (2016) also found that government's public expenditure has a negative effect on carbon emissions [33][34][35][36][37].…”
mentioning
confidence: 99%
“…Xiao et al (2013) showed that the direct impact of local government spending on CO 2 emissions was significantly negative in China [31]. Fritzsche and Jeff (2013) described a revision of the 2002 greenhouse gas emission reduction expenditure estimates made by Canadian businesses [32] , and Galinato and Galinato (2016) also found that government's public expenditure has a negative effect on carbon emissions [33][34][35][36][37].…”
mentioning
confidence: 99%
“…However, the large-scale deployment of aviation biofuels from pathways suited for aviation faces significant challenges. Examples include high production costs and the challenges of integrating aviation biofuels into regulatory regimes (Carriquiry, Du, & Timilsina, 2011;Carter, Stratton, Bredehoeft, & Hileman, 2011;Gegg, Budd, & Ison, 2014), feedstock availability and scaling-up issues (U.S. Department of Energy [DOE], 2011;Seber et al, 2014), the socio-economic and environmental consequences of large-scale changes in land use and competition with food and feed needs (Searchinger et al, 2008;Kretschmer, Narita, & Peterson, 2009;Serra & Zilbermann, 2013), the amount of water associated with biomass cultivation (Scown, Horvath, & McKone, 2011;Staples et al, 2013), and the scaling-up time required for growing biomass and building conversion facilities (Richard, 2010;Winchester, Malinab, Staples, & Barrett, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…More and more, air transport sustainability will become a real issue to be tackled appropriately, in which both aircraft manufacturers and airlines will join efforts to mitigate environmental impacts (Gohardani & Singh, 2011;Lee & Mo, 2011, Mousavi & Bossink, 2017. Renewable energy and biofuels are prominent technologies which will be mass-adopted in the 2030s, including biomass and cellulosic biofuel, and a reduction of (or zero) waste materials to achieve carbon-neutral growth, and to reduce the aviation GHG emissions (Winchester et al, 2015;IATA, 2011). In the 2030s and 2040s, new materials are likely to promote significant progress for aircraft development and products.…”
Section: Future Perspectives: the Next 75 Years (2020-2095)mentioning
confidence: 99%